High stereoselectivity on low temperature Diels-Alder reactions - da Silva Filho, Luiz Carlos; Lacerda Júnior, Valdemar; Constantino, Mauricio Gomes; da Silva, Gil Valdo José; Invernize, Paulo Roberto (Beilstein Journal of Organic Chemistry, 2005)
We have found that some of the usually poor dienophiles (2-cycloenones) can undergo Diels-Alder reaction at -78°C with unusually high stereoselectivity in the presence of niobium pentachloride as a Lewis acid catalyst. A remarkable difference in reaction rates for unsubstituted and α- or β-methyl substituted 2-cycloenones was also observed.